STUDI ANALISIS KETELITIAN GEOMETRIK CITRA SATELIT RESOLUSI TINGGI SEBAGAI PETA DASAR RENCANA DETAIL TATA RUANG PERINDUSTRIAN (STUDI KASUS : KAWASAN PT SIER SURABAYA) - Sukojo, Bangun Muljo; Mahmudi, Alfan Rozy (GEOID, 2018)
PT SIER region has an area of 245 ha. In addition, PT SIER region is divided into three sub-districts, namely Rungkut District, Tenggilis Mejoyo District, and Gunung Anyar Disrict. In the industrial area in the mapping of the region that have used a detailed map of a large scale is a scale of 1: 5000 or more. The remote sensing technology is needed for making the maps. Remote sensing technology is now used and applied in geoscience Indonesia for geospatial information on a local, regional, and globalThis research conducted data used for geometric correction is WorldView 2 satellite imagery with a spatial resolution of 2012 which is 0.46 meters and the Pleiades 1B in 2015 with a spatial resolution of 0.5 meters. In addition, the necessary data in this study are the coordinates of ground control points or so-called the Ground Control Point (GCP). The GCP coordinate data obtained from measurements in the field using geodetic GPS device. Measurements were performed using the static method for approximately 40 minutes. In doing geometric correction in this study using two methods, namely the transformation affine transformation and polynomial order 2 The results of this study indicate that the design of nets made to the GPS measurements have strength webs of 0.116274. The net strength has entered tolerance is <= 1. For the geometric correction to both images using two methods. In the method of affine value Root Mean Square Error (RMSE) for WorldView 2 is 0.306359 while the RMSE for the Pleiades 1B amounted to 0.319769. In order polynomial method 2, RMSE for WorldView 2 is 0.163263 while the RMSE for the Pleiades 1B amounted to 0.218205. The RMSE obtained both images can be used as a basis for making a map with a scale of 1: 5000